Desempenho e Rendimento de Carcaça de Frangos de Corte Submetidos a Diferentes Níveis de Treonina e Lisina, na Fase Final de Criação - Barbosa, Maria José Baptista; Junqueira, Otto Mack [UNESP]; De Oliveira Andreotti, Marcelo [UNESP]; Cancherini, Luciana Cardoso [UNESP]; Araújo, Lúcio Francelino [UNESP] (My University, 2001)
This experiment was carried out to evaluate the performance and carcass characteristics of broilers fed diets with different lysine and threonine levels, in the final phase (42 to 56 days of age). Nine hundred and seventy two male chickens were randomly assigned to nine treatments on a fatorial 3x3 (three threonine levels; 0.70; 0.77 and 0.84% and three lysine levels; 0.94; 1.04 and 1.14%), with four replicates by treatment, of 27 birds each. Weight gain, feed intake, feed conversion, carcass yield and abdominal fat were studied. Performance and carcass yield were not affected by the treatments, but tended to improve as the addition levels of the studied amino acids increased.
Evaluation of the Performance and Carcass Yield of Broilers Fed Diets with Different Threonine and Lysine Levels, in the Final Phase
Keywords: Broilers; Carcass yield; Lysine; Performance; Threonine